Improvement in Ambulatory Care Skills by Self‐administered Questionnaire through an Outpatient Training Program among Post‐graduate Young Physicians. (30th October 2015) - Hirooka, Nobutaka; Obuchi, Yasuhiro; Ono, Yosuke; Hamada, Koji; Hamano, Kunihisa; Shiraishi, Mieno; Uchida, Kosuke; Tanaka, Yuji
Abstract : Background: A lack of ambulatory care training has been reported in the literature despite the fact that many health and medical issues are handled in the ambulatory care setting. An appropriate curriculum for ambulatory care training is also yet to be established in Japan. Objective: We aimed at surveying competence in ambulatory care skills through a self‐administered questionnaire and satisfaction toward the ambulatory care training to fill the knowledge gap between ideal training and current training in the ambulatory setting. Method: We recruited all of the first year postgraduate trainees (N = 45) who rotated to the ambulatory care training program provided by the Department of General Medicine at the National Defense Medical College Hospital. Participants were asked to evaluate six skills in ambulatory care (interview, physical exam, diagnostic reasoning, therapeutic reasoning, counseling, and overall skill) and satisfaction toward the training. Results: Statistically speaking, all skills significantly improved after three months of training while some of the skills (diagnostic and therapeutic reasoning and counseling skills) improved less than the others. Satisfaction tended to be higher in the group who experienced a high number of cases. Conclusions: Ambulatory care training in a university hospital increases the ambulatory care skills by self‐administered questionnaire. A higher number of cases, supervised by faculty physicians, appears to be correlated with a higher satisfaction level to the training.